IMPLEMENTATION OF WOMEN AND CHILD PROTECTION POLICY: A STUDY ON THE PERFORMANCE EVALUATION OF CIVIL SERVANTS AT THE OFFICE OF WOMEN EMPOWERMENT, CHILD PROTECTION AND FAMILY PLANNING OF NORTH SUMATRA PROVINCE - Fathia Raisya; Syafruddin Ritonga; Beby Masitho Batubara (Pena Cendekia Insani, 2026)
This study aims to analyze the implementation of women and child protection policies through the evaluation of the performance of Civil Servants (ASN) at the Office of Women Empowerment, Child Protection and Family Planning of North Sumatra Province, as well as to identify supporting and inhibiting factors both from within (internal) and outside (external) the organization that are suspected to influence the performance achievements of ASN. In addition, the evaluation of ASN performance specifically in the context of this program has not been conducted comprehensively, thus requiring a more in-depth study. This research uses a qualitative descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation. The analysis of ASN performance refers to performance indicators according to Agus Dwiyanto, which include productivity, service quality, responsiveness, responsibility, and accountability [1]. The results show that the policy implementation has generally been carried out, but it has not been optimal. Several obstacles identified include limited human resources, coordination constraints, and uneven program socialization. Supporting factors include regulatory support, institutional commitment, and cross-sector collaboration. Therefore, strengthening human resource capacity, improving inter-agency coordination, and optimizing program socialization are needed so that the implementation of women and child protection policies can run more effectively.